An Argument for Levinasian Ethics and the Arts With Considerations for Pedagogy - Parker, Lana (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2019)
At a time when an ethics based on responsibility for the Other offers a counter to the individualism of neoliberal ideology, I argue that it is crucial to recuperate the possibility of creating the conditions for ethical moments of facing through all means possible, including art. I deliberate the possibilities for art in sustaining Levinas’s conception of an ethical intersubjective interaction, including: the call to listen to the Other, the implications of being called into question, the overflow of self, and the humility of response. To begin, I contemplate art as an Other that is able to face and break apart the bonne conscience. Second, I posit that the overflow that results from an interaction with the Other, as the bonne conscience is surpassed, can serve as a source of inspiration for artistic creation. Third, in the face of the ethical call, though one is first required to listen, one also has an obligation to respond; I contend that art can operate here, too, as a means of reply. I conclude the work with a discussion of the implications for pedagogy, including art as a means of broadening sociality.